The opioid crisis: evaluating the safety and efficacy of opioid analgesia in the management of acute post-operative dental pain. (2nd November 2021) - Merrick, Daniel; O'Sullivan, Michael; Clarke, Mary
Abstract : The use and misuse of opioid analgesics have been highlighted in recent years. This review assesses dental opioid use, the effectiveness of opioid-containing analgesics versus non-opioid alternatives and the implications for post-operative pain management strategies in the dental practice. Guidelines for the management of acute post-operative dental pain differ from country to country. The UK has a low dental opioid use rate when compared to the US. The combination of paracetamol and ibuprofen has similar, if not better, analgesic properties compared to opioid-containing alternatives, with fewer adverse effects. CPD/Clinical Relevance: Non-opioid analgesics are both a safe and effective alternative to opioid analgesics in the management of post-operative dental pain.